Clinical Importance of Duplication of Internal Jugular Vein - Kapre, Madan (Springer-Verlag, 2011)
Duplication of internal jugular vein (IJV) is rare. It is the larger channel draining the cranial cavity. We encountered duplication of the IJV while cervical node clearance in a patient with squamous cell carcinoma of left margin of the tongue. IJV divides into two parts anterior and posterior after descending about 2.5 cm from the jugular foramen. IJV is an important landmark in neck surgery. Knowledge of its variations is essential to avoid complications during surgery and to avoid misinterpretation in CT angiography.